Nail psoriasis : from A to Z - Tosti, Antonella; Rigopoulos, Dimitris (Springer International Publishing, 2014)
Nail psoriasis is very common and causes considerable morbidity to patients. With the aid of informative illustrations, this book presents the clinical signs suggestive of nail psoriasis and describes the differential diagnosis of nail abnormalities. Newer methods of diagnosis are considered, and advice is provided on the use of severity evaluation indexes. The available treatments are extensively discussed, with information on the latest options. Selection of the appropriate treatment may be a challenge, so guidance is provided on all factors that should be taken into consideration and on choice of treatment for special categories of patient, such as children and pregnant women. Contributors have been selected from across the world, offering an international perspective on the condition. Nail Psoriasis will be an invaluable up-to-date source of information for dermatologists and will also be of interest to rheumatologists and general practitioners, given that recognition of nail signs can lead to earlier diagnosis of arthropathic disease.